ANALISIS FAKTOR YANG MEMPENGARUHI KEJADIAN NEUROPATI DIABETIK PADA PASIEN DIABETES MELITUS TIPE 2 - dewi prasetyani; Dwi Martiningsih (Viva Medika, 2019)
Diabetic neuropathy is the most common complication in DM patients and can worsen the patient’s quality of life. Various studies produce different information about risk factors that cause diabetic neuropathy. This study aims to determine the dominant factors affecting the incidence of diabetic neuropathy between age, duration of diabetes, sex, HbA1c level and BMI. Rspondents were outpatient DM type 2 in Cilacap Pertamina Hospital. The number of samples 95 people taken with total sampling techniques. The incidence of diabetic neuropathy was measured using DNE scoring. Bivariate analysis used correlation test and t-test independent. Whereas multivariate analysis used multiple linear regression test. The results showed that HbA1c levels were the dominant factor influencing neuropathy diabetic (pv = 0,0005). The regression equation obtained is diabetic neuropathy = -10,8 + 0,09 age + 0,88 HbA1c level. The interpretation is diabetic neuropathy increases 0,1 times after controlling for variable HbA1c levels at each 1 year age increase. The incidence of neuropathy diabetic will be 0,8 fold higher in type 2 DM patients who experience an increase in HbA1c levels.